THE RESTORATION OF TRADITIONAL GASTRONOMY AS AN OPPORTUNITY FOR ENYIRONMENTAL AND CULTURAL TOURISM IN THE SUSTAINABLE DEYELOPMENT OF RURAL AREAS IN CILENTO (ITALY) - ALOJ, Eugenia; PEPE, Vincenzo; DE CASTRO, Mariagrazia; ZOLLO, Anna (Economic and Environmental Studies, 2020)
Cilento is a geographical territory at the Southern extremity of the Salerno Gulf and delimited in the north by the Sele River, in the east by Vallo di Diano, in the south by the Policastro Gulf and in the west by the Tirreno Sea. Cilento is well known for its coastline from Agropoli to the mouth of the Bussento River and the best known resorts are “Marina di Camerota, Capo Palinuro, Marina di Ascea, S. Maria di Castellabate”. Since 1991, almost all the area has been protected by the institution of a national park. The National Park of Cilento e Vallo di Diano (181.048 hectares) is the second largest protected area in Italy. The size of the Park determines the simultaneous presence of different areas of great natural and environmental value and beautiful landscapes. There is also historical and cultural heritage of great worth. The following three quotations reflect the most important issues for the development of the region, in which the park may play a crucial role.